Dynamic scaling equation of state for nonequilibrium solution under gravity above consolute critical temperature - Alekhin, A.D.; Ostapchuk, Yu.L. (Condensed Matter Physics, 2001)
Altitude and time dependence of nonequilibrium values of refractive index gradient for inhomogeneous methanol-hexane solution under gravity near consolute critical temperature was investigated in the work as system approaches equilibrium state. Based on these data there have been suggested scaling equations of nonequilibrium liquid under gravity for temperatures above consolute critical temperature. It has been shown that the scaling hypothesis is also valid for nonequilibrium solution close to the critical point for small values of order parameter